VD_FINDINFO Jug / 2023 / 223 vom 29. September 2022 - VD Tribunal cantonal (2022)
CONTRAVENTION, JUGE UNIQUE, CHIEN, REJET DE LA DEMANDE | 77 al. 1 LFaune, 10 CPP (CH), 398 al. 4 CPP (CH), 406 al. 1 let. c CPP (CH)